Oxygen isotopic ratios in Martian water vapour observed by ACS MIR on board the ExoMars Trace Gas Orbiter - Alday, J; Wilson, C; Irwin, P; Olsen, K; Baggio, L; Montmessin, F; Trokhimovskiy, A; Korablev, O; Fedorova, A; Belyaev, D; Grigoriev, A; Patrakeev, A; et al. (EDP Sciences, 2019)
Oxygen isotope ratios provide important constraints on the history of the Martian volatile system, revealing the impact of several processes that might fractionate them, such as atmospheric loss into space or interaction with the surface. We report infrared measurements of the Martian atmosphere obtained with the mid-infrared channel (MIR) of the Atmospheric Chemistry Suite (ACS), onboard the ExoMars Trace Gas Orbiter. Absorption lines of the three main oxygen isotopologues of water vapour (H216O, H218O, and H217O) observed in the transmission spectra allow, for the first time, the measurement of vertical profiles of the 18O/16O and 17O/16O ratios in atmospheric water vapour. The observed ratios are enriched with respect to Earth-like values (δ18O = 200 ± 80‰ and δ17O = 230 ± 110‰ corresponding to the Vienna Standard Mean Ocean Water). The vertical structure of these ratios does not appear to show significant evidence of altitudinal variations.